Is distribution of cold stenotherms constrained by temperature? The case of the Arctic fairy shrimp (Branchinecta paludosa O.F. Müller 1788). (October 2015) - Lindholm, M.; Hessen, D.O.; Færøvig, P.J.; Rognerud, B.; Andersen, T.; Stordal, F.
Abstract: Small water bodies in cold climate respond fast to global warming, and species adapted to such habitats may be valuable indicators for climate change. We investigated the geographical and physiological temperature limits of the Arctic fairy shrimp ( Branchinecta paludosa ), which is common in cold water arctic ponds, but at present retracts its range in alpine areas along its southern outreach of Norway. Seasonal logging of water temperatures along an altitudinal transect revealed an upper temperature limit of 12.7 °C for its presence, which closely matched a calculated upper temperature limit of 12.9 °C throughout its entire Norwegian range. Field data hence point to cold stenotherm features, which would be consistent with its Arctic, circumpolar distribution. Lab experiments, on the other hand, revealed a linear increase in respiration over 10–20 °C. When fed ad libitum somatic growth increased with temperature, as well, without negative physiological impacts of higher temperatures. The absence of Branchinecta paludosa in ponds warmer than 13 °C could still be due to a mismatch between temperature dependent metabolism and limited energy supply in these ultraoligotrophic water bodies. We discuss the concept of cold stenothermy in this context, and the impacts of regional warming on the future distribution of the Arctic fairy shrimp. Highlights: We explore the thermal limits for existence of the Arctic fairy shrimp B. paludosa . Logging and modelling revealed an upper thermal limit of 12.8 °C for its presence. Lab experiments did not support a distinct upper temperature threshold. Possible reasons for the patterns are discussed.